Sex Differences in Memory: Do Female Reproductive Factors Explain the Differences? - Li, Jie; Hao, Wenting; Fu, Chunying; Zhou, Chengchao; Zhu, Dongshan (Frontiers in Endocrinology, 2022)
Background: The sex differences in memory impairment were inconclusive, and the effect of female reproductive factors (age at menarche, age at menopause, and reproductive period) on the differences was not clear. We aimed to examine the sex differences in objective and subjective memory impairment in postmenopausal women and age- and education-matched men, and explore whether the differences were differed by female reproductive factors. Methods: Data were obtained from the China Health and Retirement Longitudinal Study. Using case-control matching method, 3218 paired postmenopausal women and men matched for age and education were selected. Memory was assessed using the three-word recall task and a self-rated question. Poisson regression models with a robust error variance were used. Results: The relative risk was 1.22 (95% confidence interval 1.08–1.38) for objective memory impairment in women compared with men (23.87% vs. 27.36%), and 1.51 (1.36–1.67) for subjective memory impairment (39.34% vs. 28.25%) after adjusting the confounders. The higher risk of objective memory impairment in women was different among groups of age at menarche in a linear pattern, with younger age at menarche associated with higher risks of objective memory impairment (P < 0.001 for trend). It was also different among groups of menopausal age and reproductive period in an approximate U-shaped pattern, with a similar risk of objective memory with men in women menopause at 52–53 years and having reproductive period of 31–33 years and higher risks in women with earlier or later menopause (RRs raging form 1.17 to1.41) and shorter or longer period of reproduction (RR, 1.23–1.29). The higher risks of subjective memory impairment in women were not different among different groups of reproductive factors. Conclusions: Postmenopausal women were at an increased risk of objective and subjective memory impairment than men. The higher risks in objective memory, but not subjective memory, were varied by age at menarche, age at menopause, and reproductive periods, which may help understand the underlying mechanisms of sex-differences in cognitive ageing and guide precise intervention to preventing dementia among older women and men.